The two copies of the zinc and cadmium ZIP6 transporter of Arabidopsis halleri have distinct effects on cadmium tolerance. (6th July 2020) - Spielmann, Julien; Ahmadi, Hassan; Scheepers, Maxime; Weber, Michael; Nitsche, Sarah; Carnol, Monique; Bosman, Bernard; Kroymann, Juergen; Motte, Patrick; Clemens, Stephan; Hanikenne, Marc
Abstract: Plants have the ability to colonize highly diverse environments. The zinc and cadmium hyperaccumulator Arabidopsis halleri has adapted to establish populations on soils covering an extreme range of metal availabilities. The A. halleri ZIP6 gene presents several hallmarks of hyperaccumulation candidate genes: it is constitutively highly expressed in roots and shoots and is associated with a zinc accumulation quantitative trait locus. Here, we show that AhZIP6 is duplicated in the A. halleri genome. The two copies are expressed mainly in the vasculature in both A. halleri and Arabidopsis thaliana, indicative of conserved cis regulation, and acquired partial organ specialization. Yeast complementation assays determined that AhZIP6 is a zinc and cadmium transporter. AhZIP6 silencing in A. halleri or expression in A. thaliana alters cadmium tolerance, but has no impact on zinc and cadmium accumulation. AhZIP6 ‐silenced plants display reduced cadmium uptake upon short‐term exposure, adding AhZIP6 to the limited number of Cd transporters supported by in planta evidence. Altogether, our data suggest that AhZIP6 is key to fine‐tune metal homeostasis in specific cell types. This study additionally highlights the distinct fates of duplicated genes in A. halleri . Abstract : The zinc and cadmium transporter ZIP6 alters cadmium tolerance in the metal hyperaccumulator Arabidopsis halleri . The two ZIP6 copies have organ‐specific function and control cellular metal homeostasis.